Analisis Kemampuan Penalaran Matematis Siswa Kelas VIII dalam Menyelesaikan Soal AKM Pola Bilangan Serupa PISA - Shofa, Oktavia Jauharotus; Hidayah, Indriati Nurul (Jurnal Tadris Matematika, 2024)
Mathematical reasoning is an essential competency assessed in the Asesmen Kompetensi Minimum (AKM) and PISA because it supports students in understanding and solving problems. However, studies have shown that Indonesian students’ mathematical reasoning ability is not optimal. This study employs a qualitative descriptive approach using a phenomenological framework to describe the mathematical reasoning abilities of grade VIII students in solving AKM problems related to number patterns, similar to those found in PISA, with data analysis conducted using Miles and Huberman's method. The research instruments were researchers, AKM problems of number patterns similar to PISA, and interview guidelines. Subjects were taken from each level of reasoning ability, namely the extending, consolidating, developing, beginning, and not evident levels. The results showed that students at the extended level can connect number patterns with the area of flat shapes, write patterns, use two methods, create new ideas, and show generalizations. Consolidating students are able to connect number patterns with the area of ​​flat shapes, to write properties, to find differences in patterns, to conclude, to use two methods, and to show examples of counterexamples of conjectures. Developing students can expand patterns, convert images, prove conjectures, and identify differences in patterns, but are not yet able to draw conclusions. Beginning students cannot write conjectures and patterns, make errors in writing, using, and converting units, and perform calculations. Students at the not evident level cannot convert images, are not aware of the relationship between number patterns and the area of ​​flat shapes, as well as rows and columns, and cannot make conjectures about number patterns.